International Monetary Fund Annual Report 1978. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1978)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1978. The report highlights that the period since the previous Annual Report-the third year of recovery from the most severe recession in four decades-has been one in which world economic developments were again unsatisfactory in some important respects. World output and trade continued to increase, but the pace of domestic expansion in the industrial world, which had been satisfactory during the first year or so of the recovery period, became slow and uneven, contrary to earlier expectations.